The School Age Child with Congenital Heart Disease. Issue 1 (January 2015) - Boyle, Lynn; Kelly, Michelle M.; Reynolds, Kathryn; Conlan, Misty; Taylor, Felisha
<x xml:space="preserve">Abstract</x> Abstract Currently, in the United States, there are approximately 1 in 150 adults living with congenital heart disease (CHD) (Go et al., 2014). Infant and childhood mortality related to CHD decreased by 31% between 1987 and 2005 (Khairy et al., 2010). This survival trend is predicted to increase each year due to advancements in treatment and management of CHD. This significant shift in the epidemiology of CHD requires nurses to take action in preparing children with CHD and their families for their teenage years and young adulthood. The school-age child is the ideal age to begin teaching the child about their healthcare needs and how to care for themselves in preparation for the future. The school-age child with CHD has specific physical, intellectual, emotional, and developmental needs that must be considered and managed using a multidisciplinary approach. Pediatric nurses must be aware of these needs as they help the child and their family seamlessly and successfully transition into young adulthood as a happy and healthy CHD survivor.